2020
DOI: 10.21203/rs.3.rs-113463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Robust Immune‐Associated lncRNAs Signature for Immune Checkpoint Blockade and Prognosis in Pancreatic Ductal Adenocarcinoma

Abstract: Background: An increasing body of evidence has suggested that long non-coding RNAs (lncRNAs) can serve as essential regulators in cancer immunity. We aimed to establish a robust immune-associated lncRNA signature for pancreatic ductal adenocarcinoma (PDAC) outcome prediction to enhance prognostic accuracy.Methods: Pancreatic cancer samples were obtained from the The Cancer Genome Atlas (TCGA) project. Immune‐related lncRNAs displaying significant association with overall survival (OS) were screened through uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…(4) LINC02257 was expressed at high levels in colorectal cancer patients and seemed to act as a hazard factor [ 38 ]. Xu et al noted that LINC02257 and FLVCR1-DT were utilized as an adverse lncRNA and favorable lncRNA, respectively, for monitoring the model-based prognosis prediction of PC patients [ 39 ]. RPTOR is one of the ATGs interacting with LINC02257; a study found that the expression of miR-377-3p could target RPTOR and induce autophagy in vivo and in vitro [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4) LINC02257 was expressed at high levels in colorectal cancer patients and seemed to act as a hazard factor [ 38 ]. Xu et al noted that LINC02257 and FLVCR1-DT were utilized as an adverse lncRNA and favorable lncRNA, respectively, for monitoring the model-based prognosis prediction of PC patients [ 39 ]. RPTOR is one of the ATGs interacting with LINC02257; a study found that the expression of miR-377-3p could target RPTOR and induce autophagy in vivo and in vitro [ 40 ].…”
Section: Discussionmentioning
confidence: 99%